The Pragmatic Public? The Impact of Practical Concerns on Support for Punitive and Rehabilitative Prison Policies - Vuk, Mateja (American journal of criminal justice, 2020)
Although prior investigations have not been designed to assess the issue directly and thoroughly, criminal justice research suggests that the American public supports penal policies that they believe provide utility. The public simultaneously endorses rehabilitation and punishment when they are convinced that these approaches promote general utilitarian penal goals, such as enhancing public safety. It is unclear, however, how other practical aspects of penal policies influence people’s opinions about punitive and rehabilitative prison conditions. Using a randomized experimental design, we explicitly estimate the extent to which public support for punitive and rehabilitative prison policies depends on pragmatic considerations of financial cost, ease of institutional management, and recidivism risk. Our results reveal considerable endorsement for offering rehabilitation to a hypothetical offender as well as expanding the use of such programs to other inmates. We also find less enthusiastic support for austere prison conditions. Public endorsement of both proposals showed evidence of pragmatism, though practical considerations had larger and more consistent effects on opinions about rehabilitation.